2013
DOI: 10.1111/dmcn.12313
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of ordinal scales used to classify the eating and drinking abilities of individuals with cerebral palsy

Abstract: AIM The aim of this review was to examine systematically the scope, validity, and reliability of ordinal scales used to classify the eating and drinking ability of people with cerebral palsy (CP).METHOD Six electronic databases were searched to identify measures used to classify eating and drinking ability; in addition, two databases were used to track citations of key texts. The constructs assessed by each measure were examined in relation to the World Health Organization International Classification of Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Despite the indications when referring to GT surgery, another finding of the healthcare reported in the present study, was the lack of formal tools used to assess eating abilities. This corresponds to earlier stated inconsistencies in the use of clinical measures for eating, drinking, and feeding . Moreover, the children's participation in mealtimes, whether eating orally or not, was seldom a documented area of concern.…”
Section: Discussionsupporting
confidence: 72%
“…Despite the indications when referring to GT surgery, another finding of the healthcare reported in the present study, was the lack of formal tools used to assess eating abilities. This corresponds to earlier stated inconsistencies in the use of clinical measures for eating, drinking, and feeding . Moreover, the children's participation in mealtimes, whether eating orally or not, was seldom a documented area of concern.…”
Section: Discussionsupporting
confidence: 72%
“…There is no agreement in the literature about the definition of the terms mild, moderate, and severe in relation to limitations to eating and drinking ability, or whether focus should be at the level of body functions and structures, activity, and/or participation. A recent systematic review identified the lack of a valid and reliable ordinal scale to classify the eating and drinking abilities of people with CP in both clinical and research contexts …”
mentioning
confidence: 99%
“…Measurement and classification of oropharyngeal dysphagia in children with CP have been limited by lack of consensus in terms and corresponding constructs . Terms describing ‘severity’, consistent with other domains and disciplines, have been used variably, including mild, moderate, severe, and profound oropharyngeal dysphagia . A recent review identified 15 ordinal scales classifying the eating/drinking abilities of children with CP, but concluded that none had adequate psychometric properties to meet quality standards .…”
mentioning
confidence: 99%